Control,insecticides Status Kerentanan Aedes aegypti (Diptera: Culicidae) terhadap Insektisida Malathion, Bendiokarb, dan Deltamethrin di Kota Sukabumi - Lisa Hidayati (INFOKES (Informasi Kesehatan), 2018)
Aedes aegypti L., an important vector of dengue hemorrhagic fever. Ae. aegypti control currently depends on the application of fogging focus using some chemical insecticides. Although the using of chemical insecticide inside and around homes continues to be the the principal control tool, but insecticide resistance is widespread and has been responsible for failures in control. The objective of this study is to measure susceptibility status of Aedes aegypti against insecticides. Aedes aegypti strains were collected from two locations within Cikole, Gunung Puyuh, Warudoyong, Citamiang, Cibeureum, Baros, and Lembur Situ districts in Sukabumi City, Indonesia, from May to December 2015. The research was carried out by using the method of susceptibility test (WHO 1975) which contained malathion 0.8%, bendiocarb 0.1% and deltamethrin 0.025% impragnated paper. Aedes aegypti was collected by ovitrap from 14 endemic regions in Sukabumi City. The eggs were hached and reared in laboratory until F2 generations, then treated by those insecticides. Data analysis using probit test with SPSS software ver. 15.00. According the measurement of susceptibility status can be found that all of isolates in Sukabumi were resistant to malathion with less than 80% mortality recorded 24 hours after exposure. Eight populations were moderately resistant to bendiokarb whereas 11 of strains were highly resistant to deltamethrin. These results must be considered in future control programs for Aedes aegypti, because organophosphates and pyrethroids cunently are for adult control in most countries in most areas of Indonesia.